THE EFFECT OF SLEEP HYGIENE ON INSOMNIA IN DIABETES MELLITUS PATIENTS AT ROYAL PRIMA HOSPITAL MEDAN 2024 - Tarigan, Putri Karina; Manggalika, Widya Santi; Halawa, Wirna Wati; Zega, Selvi Sri Ica Purwasih; Samosir, Andros Christopher; Anggeria, Elis (Universitas Nahdlatul Ulama Surabaya, 2025)
Introduction: Diabetes mellitus (DM) is a metabolic disorder characterized by hyperglycaemia due to abnormalities in insulin secretion, insulin action, or both. Insomnia is a common complication among DM patients and may worsen their overall condition. Objective: This study aimed to examine the effect of sleep hygiene on insomnia in 36 patients with diabetes mellitus at RSU Royal Prima Medan in 2024. Methods: A quasi-experimental one-group pre-test post-test design was employed. A total of 36 DM patients were selected using purposive sampling. Data were collected through questionnaires and analyzed using the Wilcoxon signed-rank test. Results: Before the intervention, 77.8% of patients experienced severe clinical insomnia. Following the sleep hygiene intervention, 97.2% of patients reported moderate insomnia, indicating a significant reduction in severity (p < 0.05). Conclusions: Sleep hygiene intervention significantly reduced insomnia levels in patients with diabetes mellitus. However, the study was limited by its small sample size and single-site setting, which may affect the generalizability of the results. Further research involving larger, multicenter samples is recommended.